Temperature dependence on ferroelectric properties and strain performance of PLZT ceramics containing 9 mol% La - Narit Funsueb (2020)
© 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group. PLZT ceramics containing 9 mol% La and 50–70 mol% Zr were prepared by two-stage sintering to enhance the densification and the microstructure. Dielectric properties were investigated and the phase transition from relaxor to normal ferroelectric as an increasing amount of Zr could be observed. Induced strain (butterfly loop) and polarization (hysteresis loop) were measured at the maximum electric field of 12.5 kV/cm and the temperature range of 25–140°C. It was found that temperature dependence played an important role to phase transition from ferroelectric to paraelectric, which governed polarization and strain of PLZT ceramics. Zr/Ti ratios could also determine ferroelectric and induced strain properties where morphotropic phase boundary (MPB) would maximize polarization and strain in terms of piezoelectric coefficient.